Suction-based airway clearance devices for foreign body airway obstruction: protocol for a systematic review - Palermo, Natalino; Paludi, Miguel Angel; Limonti, Francesco; Ermanno, Daniele; Semeraro, Angelica; Ganzino, Sandro; Ramacciati, Nicola (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: This paper outlines a protocol for a scoping review that will critically appraise the existing evidence base on the efficacy of airway clearance devices for foreign body airway obstruction. Methods: The search was conducted in the MEDLINE, CINAHL, the Cochrane Library, and Scopus databases. The quality, validity, and relevance of each study will be systematically evaluated using formal risk of bias/quality assessment tools, such as The Critical Appraisal and Data Extraction Tool. Results: The systematic review will identify and appraise all available studies on the efficacy of suction-based airway clearance devices for foreign body airway obstruction. The review will summarize the findings of the included studies and provide an overall assessment of the evidence on the devices’ efficacy. Conclusions: The systematic review will inform best practices in airway management by providing a comprehensive evaluation of the current literature on the effectiveness of new devices for foreign body airway obstruction treatments.